ANALISIS BIAYA DAN OUTCOME TERAPI PENGOBATAN ANEMIA PADA PASIEN GAGAL GINJAL KRONIK DENGAN TRANSFUSI DARAH DI INSTALASI RAWAT INAP RUMAH SAKIT ISLAM IBNU SINA PEKANBARU TAHUN 2012 - , AMANDA LIA HERIZA, Dr. Satibi, S.Si., M.Si., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Anemia occurs in patients with end stage of chronic renal failure, it is associated with increased of morbidity and mortality. Blood transfusion is a therapy used in anemia. The purpose of this study is to describe the treatment of anemia, the total cost of therapy needed in the treatment of anemia with blood transfusion, components that have a large contribution in the financing, factors that affect the amount of the total cost of treatment of anemia in patients with chronic renal failure and outcome of therapy. This study was conducted with non - experimental descriptive design. Methode of data collection was done retrospectively used data from medical records with a primary diagnosis of chronic renal failure who received a blood transfusion in the Ibnu Sina Pekanbaru Hospital periode of 2012 and the receipt of inpatients in the financial section. The data then processed and analyzed using descriptive methods that include: analysis of patient characteristics, analytical overview of the treatment of anemia with blood transfusion, the total treatment cost analysis, analysis of factors that affect the total cost of therapy using One - Way ANOVA, Krusskal â Wallis, and Mann - Whitney, and outcome of therapy. Researchers used analytical perspective as the perspective of the hospital. Research subjects in this study were 23 patients. Anemia therapy that used to support additional therapy with blood transfusions were folic acid and vitamin B12. The average of total cost of treatment of anemia in CRF per patient Rp.8.357.512.57 Â± 8.798.010.09. Components that contribute in making up the total cost is the cost of drug therapy of other diseases. Factors that affect the total cost of blood transfusion therapy is length of stay of patient (p = 0.027). Patients who reached the therapeutic target ( â¥ 7 g / dl ) with a blood transfusion and who have elevated levels of hemoglobin were 19 patients ( 100 % ) .